(untitled) (Fiep Bulletin - online, 2016)
Objective: To identify, from the evidence available in the literature, strategies for promoting health in the workplace and identify the main themes explored in the health promotion field in the various occupational environments. Method: Integrative Literature Review, and its execution was followed by the steps recommended by Teixeira; Lowy (2011). They used the following inclusion criteria: papers in scientific articles format, with the Medical Subject Headings: promotion and work in the title / as a matter of delimiter, in Portuguese and Spanish, with availability in full and on any date. The sample consisted of six articles that met these criteria. Results: The articles not fit into two units of meaning (specific and interdisciplinary actions) and two themes: 1) health promotion strategies in the workplace and 2) production of knowledge and the promotion of health. However, the strategies specified Work Promotion Programs with inspection and adjustments, health-promoting events, education in occupational settings; encouraging personal, family and social development; promotion of individual and organizational interventions. Conclusion: It is necessary to rethink the adopted strategies and implement actions multifocal, with intra-sectoral and intersectoral participation.